Clinical profiling of TPOAb and TGAb in patients with thyrotrophin receptor antibody-negative thyroid eye disease: A single-center observational study in China - Jing, Gaojing; Fu, Songbo; Yang, Xinji; Li, Yueyue; Ma, Rui; Wu, Wei; Tang, Xulei (Frontiers in Endocrinology, 2025)
BackgroundThyrotrophin receptor antibody (TRAb)-negative thyroid eye disease (TED) constitutes a clinically significant subset of TED, yet its features remain inadequately characterized. This study characterizes the clinical features of TRAb-negative TED patients.MethodsIn this cross-sectional study, conducted at a Chinese tertiary hospital, 86 TRAb-negative TED patients underwent comprehensive ocular examinations and thyroid function tests. Clinical characteristics were systematically analyzed.ResultsOf the 86 patients (mean age 45.24 ± 10.78 years; 53.5% female), 86.0% (n=74) exhibited bilateral ocular involvement. The primary manifestations included proptosis, eyelid edema, and eyelid retraction. The TPOAb (-)/TGAb (+) subgroup demonstrated significantly higher frequencies of eyelid erythema and lagophthalmos, along with severe NOSPECS grading, reduced visual acuity, elevated orbital pressure, and marked soft tissue involvement (all p<0.05). TPOAb-positive patients had significantly greater proptosis (p<0.05), while TGAb-positive patients showed an increased incidence of eyelid erythema (p<0.05). TGAb was identified as an independent risk factor for eyelid erythema (p<0.01).ROC analysis for TGAb predicting eyelid erythema yielded an AUC of 0.851 (sensitivity 0.778, specificity 0.831) at 3.980 IU/mL.ConclusionTRAb-negative TED displays distinct clinical features. TPOAb and TGAb levels are associated with specific manifestations, highlighting their potential value in the assessment and management of TRAb-negative TED.